2012
DOI: 10.1002/hyp.9205
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the rainfall–runoff process of the Mara River basin using the Soil and Water Assessment Tool

Abstract: Abstract:The delicate balance between human utilization and sustaining its pristine biodiversity in the Mara River basin (MRB) is being threatened because of the expansion of agriculture, deforestation, human settlement, erosion and sedimentation and extreme flow events. This study assessed the applicability of the Soil and Water Assessment Tool (SWAT) model for long-term rainfall-runoff simulation in MRB. The possibilities of combining/extending gage rainfall data with satellite rainfall estimates were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 26 publications
8
37
0
Order By: Relevance
“…The large difference in the runoff components between the two sub-catchments, demonstrates a distinct difference in the fast response characteristics between the two. These findings are supported by previous studies done by [16]. These researchers found out that Nyangores had higher infiltration than Amala.…”
Section: Partitioning Of the Flow Hydrographsupporting
confidence: 90%
“…The large difference in the runoff components between the two sub-catchments, demonstrates a distinct difference in the fast response characteristics between the two. These findings are supported by previous studies done by [16]. These researchers found out that Nyangores had higher infiltration than Amala.…”
Section: Partitioning Of the Flow Hydrographsupporting
confidence: 90%
“…The modeling results indicated that SWAT performance at the Haean catchment relied heavily on the quality and more importantly abundance of discharge data, similar to the results of Dessu and Melesse (2012). The NSE score for monitoring locations S1, S4, S5, S6, and S7 ranged between 0.64 and 0.95 with an average score of 0.76 for the 2010 calibration period and between 0.40 and 0.98 for the validation period (Fig.…”
Section: Spatiotemporal Flow Partitioning With Respect To River Dischsupporting
confidence: 68%
“…Today, high-quality land cover types can usually be acquired via remote sensing technology developed after the 1980s. Hydrological models, such as the SWAT [17,18], TOPMODEL [19], and VIC [20], are commonly used to study the effect of climate change on the hydrological cycle. Based on physical mechanisms, hydrological models offer a framework for conceptualizing and investigating the relationships between climate, land cover, and hydrological processes in various categories of time and space [21,22].…”
Section: Introductionmentioning
confidence: 99%